2012
DOI: 10.5505/tjtes.2012.58908
|View full text |Cite
|
Sign up to set email alerts
|

The impact of visits on vital signs of the patients in surgical intensive care unit: a pilot study

Abstract: AMAÇBu araştırma, yoğun bakım ünitesinde yatan hastalara yapılan ziyaretin hastanın yaşam bulguları üzerindeki etkisini incelemek amacıyla yapıldı. GEREÇ VE YÖNTEMTanımlayıcı olarak gerçekleştirilen çalışma İstanbul ilinde bir üniversite hastanesinin acil cerrahi yoğun bakım ünitesin-de gerçekleştirildi. Araştırmanın örneklemini 24 saatten fazla süre ünitede bulunan, 18 yaş ve üzeri 43 hasta oluşturdu. Verilerinin toplanmasında hastaların demografik özellikleri ile ziyaret öncesi, sırası ve sonrasındaki yaşam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
1
1
1
Order By: Relevance
“…26 A study in which patients with impaired consciousness were made to listen to music and voice messages of relatives determined that auditory stimuli increased oxygen saturation and RR. 27 Another study determined that relatives’ visits to surgical ICU patients were positively received by the patients, but the visits did not cause a significant physiological change in vital signs; 16 these results differ from those of this study. However, another study determined that auditory stimulus given to comatose patients by a family member did not cause any change in HR and RR values.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…26 A study in which patients with impaired consciousness were made to listen to music and voice messages of relatives determined that auditory stimuli increased oxygen saturation and RR. 27 Another study determined that relatives’ visits to surgical ICU patients were positively received by the patients, but the visits did not cause a significant physiological change in vital signs; 16 these results differ from those of this study. However, another study determined that auditory stimulus given to comatose patients by a family member did not cause any change in HR and RR values.…”
Section: Discussioncontrasting
confidence: 95%
“… 14 , 15 Meanwhile Karabacak et al found that visits to ICU patients had no effect on PR, respiration, BP, and SpO 2 level. 16 …”
Section: Introductionmentioning
confidence: 99%
“…Diversos estudios, han revelado que las percepciones del personal de salud, especialmente de las enfermeras, subestiman las propiedades benéficas de las visitas abiertas y, así mismo, maximizan las creencias sobre sus efectos deletéreos, sin la existencia de evidencia científica que lo sustente, de modo que los profesionales de enfermería no consideran que las políticas de visitas abiertas puedan favorecer la recuperación y mejorar el cuidado centrado en el paciente, incrementar el confort de los enfermos y proporcionar un apoyo para los cuidadores (7). De forma similar, creen que las visitas flexibles interfieren con la planeación del cuidado, incrementan el tiempo que el enfermero utiliza brindando información a los familiares, obstaculizan con el cuidado directo de enfermería, favorecen el agotamiento de los pacientes y familiares, interfieren con el humor de las enfermeras, incrementan el estrés psicológico del paciente, hacen que los profesionales se sientan controlados, generan descompensación hemodinámica en los pacientes e infringen su privacidad e incrementan el riesgo de infección (7)(8)(9)(10)(11)(12)(13)(14), por lo que restringen las visitas e implementan barreras para su flexibilización (8).…”
Section: Las Visitas En Las Unidades De Cuidado Intensivo Y Los Factounclassified